Cryptogenic Cirrhosis and Hepatopulmonary Syndrome in a Boy with Hepatic Hemangioma in Botswana: A Case Report and Review of the Literature - Francis Msume Banda; Jeremy S. Slone; Alan Anderson; Marisa Beretta; Priya Walabh; Jerome Loveland; Simon Nayler; Farirai Fani Takawira (Case Reports in Pediatrics)
Hepatic hemangiomas are considered to be the most common benign tumors of the liver. They are often found incidentally while investigating for other causes of liver disease. Hemangiomas that are less than 10 cm are not expected to cause any problems. Typically, they do not enlarge and, apart from regular follow-up, no definitive treatment is indicated. This is a posthumous case report of a male child with a medium-sized hemangioma from infancy, complicated by cryptogenic cirrhosis and hepatopulmonary syndrome. It demonstrates the challenges of managing a child with such complicated conditions in a resource-limited setting.